MODEL EVALUASI FORMATIF-SUMATIF TERHADAP MOTIVASI BELAJAR MAHASISWA PADA MATA KULIAH PERENCANAAN PENGAJARAN GEOGRAFI - Susanti Faipri Selegi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
This study aims to determine the effect of formative-sumative evaluation model on student learning motivation in geography teaching planning course. The type of this research is evaluation research with quantitative approach. Data were obtained through documentation technique and questionnaire. The collected data is processed by multiple linear regression analysis. The results of this study indicate that the summative-formative evaluation obtained an average of 73.8 and 79.4. In the internal motivation aspect, the result of the questionnaire shows that 100% of students are interested in the subject, interest / willingness to learn, curiosity, enthusiasm to ask, opinion during PBM, enthusiastic to do and complete the task, and enthusiastic in cooperation very well. While the aspect of external motivation shows that 54.8% of the facilities support the smooth learning process, the atmosphere is conducive, the results are very good, and parents are proud of the value obtained by the students. Learning by using formative-sumative evaluation model has a significant effect on students' learning motivation, as evidenced from the results of multiple linear regression analysis which shows that Fcount = 4,528 is greater than Ftable = 3.34, then Ho is rejected. Thus it is known that the formative-sumative evaluation model has a significant effect on students' learning motivation in Geography teaching planning course.